The Influence of Workload, Work Motivation, and Job Satisfaction on Employee Performance at the Lubuk Pakam Pratama Tax Services Office - Novia, Astri; Rahmadhayanti, Asita; Simatupang, Ahmad Ramadhan; Ahmadi; Helmi, Tengku Ahmad; Suprayitno, Eddi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to assess the influence of responsibility, work motivation, and job satisfaction individually and collectively on employee performance at the Lubuk Pakam Pratama Tax Services Office. The research was conducted at the Lubuk Pakam Pratama Tax Services Office, located at Jalan P. Diponegoro Number 30A, Medan, North Sumatra Region, postal code 20152, with a population of 122 individuals and a sample size of 55 individuals. Data collection involved interviews, surveys, and documentation. The data were analyzed using version 24 of the IBM Statistics for Product and Service Solution (SPSS) software, employing multiple regression analysis. Based on the findings of the study, it was observed that responsibility had a negative impact on the performance of employees at the Lubuk Pakam Pratama Tax Services Office. This was supported by the results of the t-test analysis (-3.528 < 2.008) at n = 55 with a significance level of 95%. Work motivation influenced the performance of employees at the Lubuk Pakam Pratama Tax Services Office, as evidenced by the t-test analysis (8.587 > 2.008) at n = 55 with a significance level of 95%. Job satisfaction also affected the performance of employees at the Lubuk Pakam Pratama Tax Services Office, as indicated by the t-test analysis (2.065 > 2.008) at n = 55 with a significance level of 95%. The F-test value (F-count > F table) of 36.178 > 2.79 indicates that collectively, there is a positive and significant impact of responsibility, work motivation, and job satisfaction on the performance of employees at the Lubuk Pakam Pratama Tax Services Office.